Early Childhood Caries: Epidemiology, Aetiology, and Prevention - F. Meyer; J. Enax (Hindawi Limited, 2018)
Early childhood caries (ECC) is one of the most prevalent diseases in children worldwide. ECC is driven by a dysbiotic state of oral microorganisms mainly caused by a sugar-rich diet. Additionally, poor oral hygiene or insufficient dental plaque removal leads to the rapid progression of ECC. ECC leads not only to dental destruction and pain with children, but also affects the quality of life of the caregivers. Children with extensive ECC are at high risk to develop caries with the permanent dentition or will have other problems with speaking and/or eating. To prevent ECC, several strategies should be taken into account. Children should brush their teeth with toothpastes containing gentle ingredients, such as mild surfactants and agents showing antiadherent properties regarding oral microorganisms. Parents/caregivers have to help their children with brushing the teeth. Furthermore, remineralizing and nontoxic agents should be included into the toothpaste formulation. Two promising biomimetic agents for children's oral care are amorphous calcium phosphate [Cax(PO4)yn H2O] and hydroxyapatite [Ca5(PO4)3(OH)].